A framework for evaluating branch predictors using multiple performance parameters. (5th February 2020) - Das, Moumita; Banerjee, Ansuman; Sardar, Bhaskar
Selecting a branch predictor for a program for prediction is a challenging task. The performance of a branch predictor is measured not only by the prediction accuracy – parameters like predictor size, energy expenditure, latency of execution play a key role in predictor selection. For a specific program, a predictor which provides the best results based on one of these parameters, may not be the best when some other parameter is considered. The task to select the best predictor considering all the different parameters, is therefore, a non-trivial one, and is considered one of the foremost challenges. In this paper, we propose a framework to systematically address this important challenge using the concept of aggregation and unification. For a given program, our framework considers the performance of the different predictors, with respect to the different parameters, and makes a predictor selection based on all of them. On one side, our framework can be an important aid for deciding on the best predictor to use at runtime. On the other side, the proposal of new predictor can be systematically evaluated and placed in purview of existing ones, considering the parameters of choice. We present experimental results of our framework on the Siemens, SPEC 2006 and SPEC 2017 benchmarks.